Investigation Results of State of Art Algorithms in Denoising Text Images - Emamjomeh, Nastaran (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
One of the crucial issues in acquired images is the corruption due to various kinds of noise. Recovering vital information of the original image from the noisy image is the purpose of image denoising. Denoising text images is of special interest since they convey important information. They are, however, corrupted by noise due to scanning, transfer or digitization. Old document images which date back to many years are affected by noise and deteriorations more seriously. Some of the deteriorations include ink-leakage from the black page, brown depigmentation of paper, fading text, background points. Reduction of noise, or denoising, is a vital step in the image processing of documents. Various methods for decreasing noise have been proposed by researchers already. Weighted Nuclear Norm Minimization (WNNM) will employ the low-rank standard. This algorithm uses low-rank models and produces good denoising results. This thesis applies WNNM method to different text images and compares this method with some other traditional denoising methods, such as Block Matching and 3D Filtering (BM3D), Non-local Centralized Sparse Representation (NCSR), and Expected Patch Log Likelihood (EPLL). A preliminary investigation of the various methods is also carried out for some ancient document images. The results show that using the WNNM method and denoised images have a higher peak signal-to-noise ratio (PSNR) than other methods. For example, for 𝜎 = 10, WNNM denoised images in average have PSNR=32.21, while BM3D denoised images in average have PSNR=31.84, EPLL denoised images have PSNR=31.47, and NCSR denoised images have PSNR=31.93.

ÖZ: Edinilen görüntülerdeki önemli konulardan biri, çeşitli gürültüler nedeniyle oluşan bozulmadır. Orijinal görüntünün hayati bilgilerini gürültülü görüntüden kurtarmak, görüntü denoising'in amacıdır. Metin görüntülerinin devaziyesi, önemli bilgiler aktardıkları için özel ilgi çekicidir. Bununla birlikte, tarama, aktarım veya dijitalleştirme nedeniyle gürültü nedeniyle bozulurlar. Uzun yıllara dayanan eski belge görüntüleri gürültüden ve bozulmalardan daha ciddi şekilde etkilenir. Bozulmalardan bazıları siyah sayfadan mürekkep sızıntısı, kağıdın kahverengi depigmentasyonu, solgun metin, arka plan noktalarıdır. Gürültünün azaltılması veya denoising, belgelerin görüntü işlenmesinde hayati bir adımdır. Gürültüyü azaltmak için çeşitli yöntemler araştırmacılar tarafından zaten önerilmiştir. Ağırlıklı Nükleer Norm En Aza İndirme (WNNM) düşük dereceli standardı kullanacaktır. Bu algoritma düşük dereceli modeller kullanır ve iyi denoising sonuçları üretir. Bu tez, farklı metin görüntülerine WNNM yöntemi uygular ve bu yöntemi Blok Eşleştirme ve 3B Filtreleme (BM3D), Yerel Olmayan Seyrek Gösterim (NCSR) ve Beklenen Düzeltme Eki Günlüğü Olasılığı (EPLL) gibi diğer bazı geleneksel denoising yöntemleriyle karşılaştırır. Bazı eski belge görüntüleri için çeşitli yöntemlerin ön araştırması da yapılmaktadır. Sonuçlar, WNNM yöntemini ve denoised görüntüleri kullanmanın diğer yöntemlere göre daha yüksek bir tepe sinyalgürültü oranına (PSNR) sahip olduğunu göstermektedir. Örneğin, σ=10 için WNNM denoised görüntüler ortalama PSNR=32.21, BM3D denoised görüntüler ortalama PSNR =31.84, EPLL denoised görüntüler PSNR =31.47 ve NCSR denoised görüntüler PSNR = 31.93 vardır.
Master of Science in Electrical and Electronic Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2021. Supervisor: Prof. Dr. Hüseyin Özkaramanlı.Abstract:
Keywords: Thesis Tez; Electrical and Electronic Engineering Department; Computer vision; Image processing--Digital techniques; Image Analysis; Image Processing; Image Denoising; Text Image Denoising; Weighted Nuclear Norm Minimization Algorithm; Low-rank Minimization